Inter-religious Marriage in Indonesia: Pros and Cons in the Administrative and Constitutional Law - Romadhon, Adzkia Dzikro; Bahori, Adibah (Indonesian State Law Review (ISLRev), 2023)
Inter-religious marriage is a complex and multifaceted issue in Indonesia, a diverse nation with a majority Muslim population. This paper explores the legal landscape surrounding inter-religious marriages in Indonesia, focusing on both the administrative and constitutional dimensions. The study aims to analyze the advantages and disadvantages of the existing legal framework governing inter-religious marriages, shedding light on the implications for individuals, families, and society. The administrative aspects of inter-religious marriage involve the bureaucratic processes and legal requirements that couples must navigate to register their unions. This paper examines the administrative challenges faced by inter-religious couples, exploring issues such as documentation, consent, and the role of government institutions in facilitating or impeding such marriages. On the constitutional front, the study delves into the legal principles and rights enshrined in Indonesia's constitution that pertain to inter-religious marriages. The analysis considers the constitutional guarantees of religious freedom, equality, and non-discrimination, as well as potential conflicts with other constitutional provisions. The pros and cons of inter-religious marriages are discussed, considering the social, cultural, and economic implications for individuals and their communities. Positive aspects such as fostering social cohesion, cultural diversity, and personal freedom are contrasted with challenges like societal resistance, legal complexities, and potential impacts on children within these unions. Furthermore, the paper examines recent developments and debates surrounding legislative reforms related to inter-religious marriages in Indonesia. It evaluates the potential for legal changes to address existing challenges and enhance the protection of individual rights while respecting the diverse religious landscape of the nation. In conclusion, this paper offers a comprehensive analysis of inter-religious marriage in Indonesia, exploring both administrative and constitutional aspects. By presenting a nuanced understanding of the pros and cons, it contributes to the ongoing discourse on legal reforms and social attitudes towards inter-religious unions, aiming to promote a more inclusive and equitable legal framework for all citizens.